2012
DOI: 10.3389/fpsyg.2012.00015
|View full text |Cite
|
Sign up to set email alerts
|

Attention, Awareness, and the Perception of Auditory Scenes

Abstract: Auditory perception and cognition entails both low-level and high-level processes, which are likely to interact with each other to create our rich conscious experience of soundscapes. Recent research that we review has revealed numerous influences of high-level factors, such as attention, intention, and prior experience, on conscious auditory perception. And recently, studies have shown that auditory scene analysis tasks can exhibit multistability in a manner very similar to ambiguous visual stimuli, presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 204 publications
4
99
0
Order By: Relevance
“…How can I use this information to plan an action? (3) Although attention is not always necessary, our awareness of a sound can be influenced by attention (Alain and Arnott 2000;Micheyl et al 2003;Fritz et al 2005;Shinn-Cunningham 2008;Snyder et al 2012;Gutschalk et al 2015). For example, we can choose whether to listen to-or ignore-the first violin, the string section, or even the whole orchestra.…”
Section: Introductionmentioning
confidence: 99%
“…How can I use this information to plan an action? (3) Although attention is not always necessary, our awareness of a sound can be influenced by attention (Alain and Arnott 2000;Micheyl et al 2003;Fritz et al 2005;Shinn-Cunningham 2008;Snyder et al 2012;Gutschalk et al 2015). For example, we can choose whether to listen to-or ignore-the first violin, the string section, or even the whole orchestra.…”
Section: Introductionmentioning
confidence: 99%
“…This is sometimes called 'bottom-up' processing and the stages can range from low-level to high-level. However, it is now acknowledged that the flow of processing is not unidirectional [21,22], and that there are strong 'top-down' influences from factors such as attention, the goals of the individual in the specific situation, expectations and prior knowledge [9,[23][24][25]. The relative influence of bottom-up and top-down processes and the way that they interact remain unclear.…”
Section: Revising the Hierarchical Framework For Scene Analysismentioning
confidence: 99%
“…Interest in top-down effects on auditory scene analysis has grown in recent years [24,25,29]. There is no doubt that perceptual experience can be modified by attention or intention [23] and by previous experience [17], in a way that is specific for each individual.…”
Section: The Role Of Salience and Attention In Scene Analysismentioning
confidence: 99%
“…However, in these studies, listeners were actively searching for familiar melodies, thus they intentionally attempted to segregate the interleaved sequences as it helped them to detect the target patterns. Several studies (e.g., McDermott et al, 2011) showed that familiarity with some given sounds (either through previous knowledge or exposure to the sounds prior to testing them as part of a mixture) enhances the likelihood of segregating them from other concurrent sounds even without the listener actively searching for the familiar sounds (for a review, see Snyder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%